Revision of the Stochastically Perturbed Parametrisations model uncertainty scheme in the Integrated Forecasting System. (16th February 2021) - Lang, Simon T. K.; Lock, Sarah‐Jane; Leutbecher, Martin; Bechtold, Peter; Forbes, Richard M.
Abstract: The Stochastically Perturbed Parametrisations scheme (SPP) represents model uncertainty in numerical weather prediction by introducing stochastic perturbations into the physical parametrisation schemes. The perturbations are constructed in such a way that the internal consistency of the physical parametrisation schemes is preserved. We developed a revised version of SPP for the Integrated Forecasting System of the European Centre for Medium‐Range Weather Forecasts (ECMWF). The revised version introduces perturbations to additional quantities and modifies the probability distributions sampled by the scheme. Medium‐range ensemble forecasts with the revised SPP are considerably more skilful than ensemble forecasts with the original implementation of SPP. The revised version of SPP is similar, in terms of forecast skill, to the Stochastically Perturbed Parametrisation Tendency scheme (SPPT), which is currently used to represent model uncertainty in the operational ECMWF ensemble forecasts. Abstract : Medium‐range ensemble forecasts with a revised version of the Stochastically Perturbed Parametrisations model uncertainty scheme (SPP) are considerably more skilful than ensemble forecasts with the original implementation of SPP. The revised version introduces perturbations to additional quantities and modifies the probability distributions sampled by the scheme. The new revised version of SPP is similar, in terms of forecast skill, to the Stochastically Perturbed Parametrisation Tendency scheme (SPPT), which is currently used to represent model uncertainty in the operational ECMWF ensemble forecasts.